Bosea caraganae sp. nov. a new species of slow-growing bacteria isolated from root nodules of the relict species Caragana jubata (Pall.) Poir. originating from Mongolia. Issue 9 (5th June 2019) - Sazanova, Anna L.; Safronova, Vera I.; Kuznetsova, Irina G.; Karlov, Denis S.; Belimov, Andrey A.; Andronov, Evgeny E.; Chirak, Elizaveta R.; Popova, Janna P.; Verkhozina, Alla V.; Willems, Anne; Tikhonovich, Igor A.
Abstract : Two Gram-stain-negative strains, RCAM04680 T and RCAM04685, were isolated from root nodules of the relict legume Caragana jubata (Pall.) Poir. originating from the south-western shore of Lake Khuvsgul (Mongolia). The 16S rRNA gene ( rrs ) sequencing data showed that these novel isolates belong to the genus Bosea and are phylogenetically closest to the type strains Bosea lathyri LMG 26379 T, Bosea vaviloviae LMG 28367 T, Bosea massiliensis LMG 26221 T and Bosea lupini LMG 26383 T (the rrs -similarity levels were 98.7–98.8 %). The recA gene of strain RCAM04680 T showed the highest sequence similarity to the type strain B. lupini LMG 26383 T (95.4 %), while its atpD gene was closest to that of B. lathyri LMG 26379 T (94.4 %). The ITS, dnaK and gyrB sequences of this isolate were most similar to the B. vaviloviae LMG 28367 T (86.8 % for ITS, 90.4 % for the other genes). The most abundant fatty acid was C18 : 1 ω7 c (40.8 %). The whole genomes of strains RCAM04680 T and RCAM04685 were identical (100 % average nucleotide identity). The highest average nucleotide identity value (82.8 %) was found between the genome of strain RCAM04680 T and B. vaviloviae LMG 28367 T . The common nod ABC genes required for legume nodulation were absent in both strains; however, some other symbiotic nol, nod, nif and fix genes were detected. Based on the genetic study, as well as analyses of the whole-cell fatty acid compositions and phenotypic properties, a new species, Bosea caraganae sp. nov. (type strain RCAM04680 T (=LMG 31125 T ), is proposed.